X-band metamaterial absorber with dual band/broadband absorption characteristics - Agarwal M.; Meshram M.K. (My University, 2025)
A compact metamaterial absorber working in X-band is presented in this paper. The unit cell consists of square patch enclosed within the square shaped closed ring resonator (CRR) and diagonally connected with each other via a tilted strip. The proposed structure is having dual band absorbance with peak absorptivity of 95.16% and 97.84% at 8.70 GHz and 10.64 GHz, respectively. Furthermore, broadband absorbance is achieved from the same structure by adjusting the design parameters. The broadband absorber is having over 90% absorbance from 8.50-11.13 GHz. The experimental Full width at Half Maximum (FWHM) bandwidth of the broadband absorber is 3.57 GHz. Both the absorbers have identical absorbance characteristics for two orthogonal polarizations (TE and TM). Moreover, the proposed structure is working well for wide angles of incident wave up to 600. Power loss density in the dielectric and at resonator surface of broadband absorber is also calculated. © 2015 IEEE.